Successful Control of Late‐Onset Nephrotic Syndrome in FN1 ‐Associated Fibronectin Glomerulopathy: A 17‐Year Clinical Course - Nobuhiro Kanazawa; Masayuki Iyoda; Kazuki Abe; Taihei Suzuki; Yoko Shirai; Kenichiro Miura; Kazuho Honda; Hirokazu Honda (Nephrology, 2026)
ABSTRACT Fibronectin glomerulopathy (FNG) is a rare renal disorder characterized by excessive glomerular fibronectin deposition, often associated with variants in the fibronectin 1 ( FN1 ) gene. Clinically, FNG presents with proteinuria, hematuria, and hypertension, and may progress to end‐stage kidney disease. However, its long‐term clinical course and optimal management remain incompletely defined. We report a sporadic case of FNG in a 26‐year‐old woman carrying an FN1 variant, c.2918A > G (NM_212482.4). Seventeen years after initial detection of proteinuria, she developed nephrotic syndrome with generalized edema. Supportive therapy, including renin–angiotensin system inhibitors and diuretics, was insufficient, and prednisolone and cyclosporine A were initiated for management of nephrotic syndrome. The patient subsequently achieved partial remission, with urinary protein decreasing to < 1 g/gCr and no major adverse events. During tapering of immunosuppression, a sodium–glucose cotransporter 2 (SGLT2) inhibitor was added as adjunct therapy. This case suggests a potential role for immunosuppressive therapy in management of late‐onset nephrotic syndrome associated with FNG, with SGLT2 inhibition potentially contributing to maintenance of remission.